1985
DOI: 10.1007/bf01329266
|View full text |Cite
|
Sign up to set email alerts
|

A new interpretation of viscosity and yield stress in dense slurries: Coal and other irregular particles

Abstract: Illinois coal was ground and wet-sieved to prepare three powder stocks whose particle-size distributions were characterized. Three suspending fluids were used (glycerin, bromonaphthalene, Aroclor), with viscosities ~/$ that differed by a factor of 100 and with very different chemistries, but whose densities matched that of the coal. Suspensions were prepared under vacuum, with coal volume fractions ¢ that ranged up to 0.46. Viscosities were measured in a cone-and-plate over a shear rate (9) range 10-3-102s -1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 17 publications
3
28
0
1
Order By: Relevance
“…In this case, the authors attributed yielding behavior to either particle jams or weak polymer-particle interactions, but they did not provide quantitative justification in their explanations. Such behavior was also observed by Wildemuth and Williams [238] with coal-glycerin slurries, Kytömaa and Prasad [144,197] with 2 mm glass beads in a water-glycerol solution, Coussot [65] with 100 m polystyrene beads in water-glycerol solutions, and Johma et al [134] with 2 m polystyrene beads in water. In the latter case, the authors related the yield appearance to structural changes in the particle arrangement (glass transition) at a critical solid concentration (φ = 0.58).…”
Section: Constitutive Equations: Physical Origin Of the Yield Stressmentioning
confidence: 62%
“…In this case, the authors attributed yielding behavior to either particle jams or weak polymer-particle interactions, but they did not provide quantitative justification in their explanations. Such behavior was also observed by Wildemuth and Williams [238] with coal-glycerin slurries, Kytömaa and Prasad [144,197] with 2 mm glass beads in a water-glycerol solution, Coussot [65] with 100 m polystyrene beads in water-glycerol solutions, and Johma et al [134] with 2 m polystyrene beads in water. In the latter case, the authors related the yield appearance to structural changes in the particle arrangement (glass transition) at a critical solid concentration (φ = 0.58).…”
Section: Constitutive Equations: Physical Origin Of the Yield Stressmentioning
confidence: 62%
“…Several authors have documented the existence of a yield stress in the limit of vanishing shear rate. [2][3][4] During the early attempts to model yield stress in non-colloidal systems, a popular idea was that the yield stress arises from the dependence of the maximum solid concentration on the shear stress. 2,5 Another explanation lies in the process of particle settling where frictional contacts between particles generate Coulomb friction on the bulk scale.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] During the early attempts to model yield stress in non-colloidal systems, a popular idea was that the yield stress arises from the dependence of the maximum solid concentration on the shear stress. 2,5 Another explanation lies in the process of particle settling where frictional contacts between particles generate Coulomb friction on the bulk scale. 6,7 Using magnetic resonance imaging, Ovarlez, Bertrand, and Rodts 8 measured the velocity and concentration profiles inside a wide-gap coaxial-cylinder rheometer.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that this yield stress increased dramatically when the solid concentration approached its densest packing. Ancey [1] mentions other supporting evidences for such a yield stress and quotes Wildemuth and Williams' [44] yield stress formula…”
Section: Viscous Stress Parameterization Based On Viscometric Considementioning
confidence: 96%